The dimensions of transformational leadership of women library leaders / Nik Nur Izzati Nik Rosli... [et al.] - Nik Rosli, Nik Nur Izzati; Mohd Shukry, Amira Idayu; Johari, Nor Farizah; Md Arifin, Noor Arina (Universiti Teknologi MARA Cawangan Pahang, 2017)
This study is conducted to identify whether transformational leadership is being practiced by women library leaders in university libraries in Malaysia. There are four dimensions of transformational leadership qualities namely, inspirational leadership, idealized influence, intellectual stimulation, individualized consideration and they are held to have a relationship on the performance of leaders in organizations. Questionnaires were distributed to 200 professional librarians in seven public university libraries where the Chief Librarian is a woman and they were being assessed by the librarians in their library. The findings revealed that the four transformational leadership qualities exist among women library leaders in public university libraries. The result shows that the staff perceived that women library leaders practiced transformational leadership. Respondents agreed that their leaders have the transformational leadership qualities and rated highest score in idealized influence (4.15) and lowest in individualized considerations (3.95). Furthermore, a positive relationship exists between transformational leadership qualities and performance of the women library leaders in university libraries in Malaysia. This implies that a leader who has the high level of transformational leadership qualities will likely to have high level of work performance